2017
DOI: 10.1111/ijfs.13456
|View full text |Cite
|
Sign up to set email alerts
|

Stir‐frying treatments affect the phenolics profiles and cellular antioxidant activity of Adinandra nitida tea (Shiyacha) in daily tea model

Abstract: Summary Adinandra nitida tea (Shiyacha) is a well‐known resource of functional foods with many healthful features. Effect of stir frying on phenolics, aromatic compounds, cellular antioxidant and antiproliferative activities in A. nitida tea was investigated. Stir‐fried samples depicted a significant increase in total water‐soluble solid, phenolics and flavonoids contents, respectively. In stir‐fried treated samples, main compounds were higher than in corresponding untreated samples. Similar trend was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In addition, few changes were observed in TPC and TFC after heat treatment at 100 °C and 125 °C, while both were significantly elevated ( p < 0.05) to 252.23 mg GAE per g DW and 461.68 mg RE per g DW, respectively, by further heating to 150 °C. The results agreed with Chen et al , 33 who reported a significant increase in phenolic and flavonoid contents of A. nitida leaves after stir-frying. It may be due to cell wall disruption; that is, heat induced the breakdown of lignocellulosic structure of the ANE, thereby releasing flavonoids and phenols.…”
Section: Resultssupporting
confidence: 92%
“…In addition, few changes were observed in TPC and TFC after heat treatment at 100 °C and 125 °C, while both were significantly elevated ( p < 0.05) to 252.23 mg GAE per g DW and 461.68 mg RE per g DW, respectively, by further heating to 150 °C. The results agreed with Chen et al , 33 who reported a significant increase in phenolic and flavonoid contents of A. nitida leaves after stir-frying. It may be due to cell wall disruption; that is, heat induced the breakdown of lignocellulosic structure of the ANE, thereby releasing flavonoids and phenols.…”
Section: Resultssupporting
confidence: 92%
“…Consequently, in the present study, free radical scavenging and total antioxidant capacity (TOC) of edible wild fruits were evaluated by DPPH, OH − , H 2 O 2 , PMA, and FRAP assays. The scavenging of free radical increases with increasing percentage of their inhibition [53, 54]. Therefore, use of different methods (DPPH, OH − , and H 2 O 2 ) is helpful to fully explain the antioxidant capacity in plants' extract.…”
Section: Resultsmentioning
confidence: 99%
“…36 For example, in stir-fried-treated Adinandra nitida tea, a well-known resource of functional foods, the main compounds such as total water-soluble solids, phenolics and flavonoids content were higher than in the corresponding untreated samples. 38 Bai-Zhu possesses significantly different therapeutic effects as compared to processed Bai-Zhu since the processing increases the content of atractylenolide, which could strengthen the effect on gastrointestinal function. 3 There are no studies on the processing of S. oblata at home and abroad.…”
Section: Discussionmentioning
confidence: 99%